IMPLEMENTASI SISTEM PEMBAYARAN TIKET DENGAN E-MONEY (BRIZZI) PADA PT. ASDP (Studi Pada Pelabuhan Penyeberangan Bolok Kupang) - Senmalai, Jefriyantho; Ballo, Fransina W.; Tungga, Cicilia A. (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 13 No 12 (2024): Vol.13.No.12. DESEMBER 2024 [831-914]DO - 10.24843/EEP.2024.v13.i12.p05, 2025)
Implementation of a ticket payment system is a system that includes regulations, contracts/agreements, operational facilities, and technical mechanisms used for delivering, validating and receiving ticket payment instructions, as well as fulfilling payment obligations through the exchange of "value" between individuals, banks and other institutions. both domestic and cross border between countries. The aim of this research is to explain the implementation of the ticket payment system with E-Money BRIZZI at the Bolok Kupang Ferry Port. This research was conducted using qualitative methods and used secondary data obtained from PT. ASDP Kupang Branch, as well as primary data obtained from interviews with 12 informants who were determined using a purposive sampling technique. The informant that researchers used in this research was the Business Manager of PT. ASDP Kupang Branch, Head of Counter PT. ASDP Kupang Branch, and people who use BRIZZI cards The results of this research show that the implementation of the ticket payment system using BRIZZI cards is running well and in accordance with the management mechanism of PT. ASDP Kupang Branch. Keywords: Service Strategy, E-money (BRIZZI), PT. ASDP Kupang Branch